Strategi Inkuiri Augmented Reality dengan Aplikasi Merge Cube untuk Materi IPA di Sekolah Dasar - Taufik Afandi; Muhlisin Muhlisin; Abdul Khobir (Jurnal Pendidikan dan Sastra Inggris, 2025)
The decline in students' interest in learning science in elementary schools is a crucial issue that affects their in-depth understanding of scientific concepts. This research aims to develop and analyze the effectiveness of an inquiry learning strategy based on Augmented Reality (AR) with the Merge Cube application in increasing student engagement and understanding of science material. The research method used is development research (R&D) with a quasi-experimental approach, involving elementary school students as subjects. Data was collected through observation, learning results tests, and student response questionnaires. The research results show that the application of inquiry strategies with the support of Merge Cube significantly increases students' conceptual understanding, science process skills and learning motivation. Findings also show that AR-based learning experiences create more interactive and contextual learning. In conclusion, the integration of AR technology in an inquiry approach is an effective strategy for science learning in elementary schools. Researchers recommend the use of AR media such as the Merge Cube as a learning innovation at the elementary level, as well as teacher training to optimize its use in the classroom.